DEVELOPING STUDENTS' NATURAL SCIENCE LITERACY THROUGH THE PISA INTERNATIONAL ASSESSMENT PROGRAM (Conference Zone, 2021)
This article focuses on the development of students' natural literacy based on PISA assignments. Samples from PISA assignments are provided.